Manoel Monteiro: a trajetória e a inserção da literatura de folhetos (2000-2012). - Rosário, Maria Helena do (2021)
This report assesses poet Manoel Monteiro's life, author of an extensive collection of booklets. 'Folhetos' booklets are a branch of literature, originated in Iberian Península, that entered the Northeast Region of Brazil during XVIII century. The major features of 'cordel' literature compounds a unique group characterized by simple language, diverse subjects, low price and others. Monteiro was bom in the City of Bezerros, Pernambuco, 04/02/1937, in the Northeast Region of Brazi. When he was 6 years old, he used to visit the city's fair along his father. There he became passionate about 'cordel' after seeing local poets selling their booklets. At that moment, he decided his lifestyle and profession: to become a Poet. When 16 years old, Monteiro moved to Campina Grande City, in Paraíba State, where he started his booklet production. His most prolific period spans from 2000 to 2012. Schools at the State of Paraíba have used Monteiro's books and 'cordel' booklets as educational material as Monteiro's work has a straightforward language. His 'cordel' works discuss current relevant topics including ecology, health, grammar, literature, and behaviour.